Incidencia de la calidad de agua potable en el consumo diario residencial en poblaciones menores a 150.000 habitantes - Lindao Rosero, Verónica Karina (2018)
Having a large coverage of basic services does not guarantee the quality of them. Providing an endowment that satisfies the entire population is one of the constant problems due to the scarcity of sources and population growth, so the distribution of quality water is one of the biggest challenges for the governments in charge, but what occurs, when this does not happen ¿ How does it affect the population? knowing how quality influences daily consumption will reveal the current problems of our networks and will allow us to design strategies for rational use and health care. The main objective of this research was to analyze the incidence of drinking water quality in daily consumption in the residential sector, from 11 populations under 150,000 inhabitants in Ecuador. For which, supported by the method of urban and socioeconomic characterization and determination of 4 population ranges, several variables were analyzed in terms of quality (Ingecap) to determine how these affect consumption among which we have use of water barrels, organoleptic perceptions and type of storage. Within the procedure we used the analysis of variance, Tukey comparison test, linear trends, coefficient of determination (R²) and correlation (R), supported by a descriptive statistic. As a results, its determined that the quality of drinking water does affect daily consumption, that mistrust in the water network leads to a significant consumption of water barrels in all populations.